Abdominal angiostrongyliasis: pathologic findings in Swiss mice infected with different doses of Angiostrongylus costaricensis. (7th July 2020) - Hermes, C.C.; Benvegnú, E.; Costa, M.M.; Rodriguez, R.; Vieira, M.I.B.
Abstract: Abdominal angiostrongyliasis is caused by Angiostrongylus costaricensis, the definitive and intermediate hosts of which are wild rodents and terrestrial molluscs, respectively. Humans are accidental hosts and can be infected by ingesting the third-stage (infective) larvae (L3). It remains unclear whether the number of L3 inoculated is related to lesion severity. Our aim was to analyse histopathological alterations in Swiss mice infected with different doses of A. costaricensis. Thirty-two mice were randomly divided into four groups ( n = 8/group): uninfected, control mice; mice infected with a low dose (five L3); mice infected with an intermediate dose (15 L3); and mice infected with a high dose (30 L3). The frequency of intestinal thrombi, splenitis, eggs/larvae, hepatic infarction and acute pancreatitis differed among the groups, the last being considered a significant finding. We conclude that different infective doses alter the histopathological aspects of the infection in Swiss mice, those aspects being more pronounced at medium and high doses, with no effect on the development of the disease. This experimental model shows that the parasite life cycle can be maintained in Swiss mice through the inoculation of a low dose (five L3).